Analisis Faktor yang Mempengaruhi Minat Belajar pada Pembelajaran Daring Mahasiswa Pendidikan Ekonomi FKIP UNRI - Yumelda Sari; Gimin Gimin; RM Riadi (Departement of Mathematics Education, 2023)
This study aims to determine the factors that influence learning interest in online learning of Economics Education FKIP UNRI students. The population in this study were students of the Department of Economics Education FKIP UNRI and the sample in this study used a purposive sampling method, which is a sampling technique in which all members of the population were sampled as many as 159 students. The data collection method in this study used a questionnaire. Data were analyzed by multiple linear regression analysis. The results showed that the factors affecting interest had a significant effect on the online learning interest of students of Economics Education FKIPa UNRI class of 2018-2020 with the regression equation Y=19.353 +2651+4052+1843+4864+854+e and contributed 22.9% to the factors that affect interest in learning